The First Family Cluster of COVID-19 in Bangladesh- Enigma in Developing Country (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Currently 221 countries of the globe is affected with COVID- 19 pandemic caused by a novel corona virus naming SARSCoV- 2 and leads to more than 4000000 confirmed cases and more than 300000 death already. The South East Asia regions have many LMIC status where the health system is disorganized and less prepared than what it should be. Although India and Pakistan started to react against the pandemic with multiple strategy to combat the bloom of the epidemic, Bangladesh was relaxing as there were lack of confirmation of cases and although the country has prolonged period of time to combat the pandemic situation, it was not proactive from the beginning. Inappropriate screening at entry, poor quarantine process and gross lack of infection prevention and control measure leads to observe the confirmed cases to develop one by one. Even in this conservative testing approach of Bangladesh, a family of cluster (6 members) of confirmed COVID 19 was observed with development of huge question in health care system.J Bangladesh Coll Phys Surg 2020; 38(0): 141-144